Students' Mathematical Critical Thinking Ability In Problem-Based Learning Assisted With Interactive Media With Ethnomathematic Nuances - Fikri Arif, Dimas Sofri; Mastur, Zaenuri; Cahyono, Adi Nur (Integral (Jurnal Penelitian Pendidikan Matematika), 2023)
Indonesian students' critical thinking ability is still low. The lack of critical thinking skills occurs because students tend to memorize material and formulas rather than understand concepts, so that students are less trained in developing critical thinking skills.QThe aims of this study were (1) to find out the effectiveness of the problem-based learning model assisted by interactive media with ethnomathematics nuances on the mathematical critical thinking skills of Grade VIII students of SMP Negeri 1 Adiwerna. The population in this study were students of class VIII SMP Negeri 1 Adiwerna Tegal Regency for the academic year 2021/2022 consisting of 9 classes. The sample in this study was class 8I as an experimental class that was given learning using a problem-based learning model assisted by interactive media, class 8F as a control class that was given expository model learning and class 8A as a trial class. The research method used in this research is Quasi Experiment with Nonequivalent Control Group Design. In this design, there are two groups selected by cluster random sampling. The research procedure consisted of four stages, namely the planning stage, the implementation stage, the data analysis stage and the conclusion drawing stage. Data collection techniques in this study include documentation, questionnaires, and tests. Data analysis techniques in this study were individual completeness tests, classical completeness tests, average similarity tests. The results of this study are (1) the problem based learning model assisted by interactive media with ethnomathematics nuances is effective for mathematical critical thinking skills.